Accuracy assessment of combined diffusion weighed and dynamic gadolinium MR sequences in characterization of salivary gland tumors - Lamya Eissa (The Egyptian Journal of Radiology and Nuclear Medicine, 2016)
Background: The salivary glandular tumors are challenging as regards preoperative diagnosis and MRI with the use of DWI and DCE are evaluated in accuracy for characterization of salivary masses. Methods: The study included 53 patients who underwent MRI-DWI and DCE and diagnosis was made by diagnostic scheme of ADC-values and four types of DCE curves. Results: Pleomorphic adenomas had the highest of all ADC values on DWI (⩾1.4 × 10−3 cm2/s), and Warthin tumors had low values (0.6–0.8 × 10−3 cm2/s), while malignant tumors had intermediate values (0.8–1.2 × 10−3 cm2/s). Type A curve predominated the pleomorphic adenomas, type B curve predominated Warthin, and other lymphoid lesions as lymphoma. Type C curve predominated malignant lesions. Statistical analysis showed combination intermediate ADC (in range of 0.8 to <1.4 × 10−3 cm2/s) and type C as useful test of malignancy with high accuracy of 90.5%. Conclusion: DWI and dynamic enhancement curves with combined interpretation of both techniques and in view of the concluded values can provide valuable data in characterization of salivary glandular tumors.